EVALUASI PROGRAM PERPUSTAKAAN KELILING DINAS PERPUSTAKAAN DAN KEARSIPAN KABUPATEN ACEH TENGAH - Simahara, Bengini; Zunafriesma, Nanda; Nova, Irhamna Sahru (Saraq Opat: Jurnal Administrasi Publik, 2023)
In Law Number 43 of 2007 concerning libraries, a library is defined as an institution that manages written works, printed works, and/or recorded works in a professional manner with a standardized system to meet the educational, research, preservation, information, and recreational needs of users. Mobile Library Program of Central Aceh Library and Archives Service in 2017. This study aims to evaluate the Mobile Library Program in Central Aceh District. This type of research is descriptive qualitative. The informants for this study included the Head of the Central Aceh District Library and Archives Service, schools that had mobile library programs in Central Aceh District, the community, and related stakeholders. The results showed that the mobile library program was ineffective as a whole because meeting the needs for books and providing services was only for junior high schools (SMP) and high schools (SMA) in the Central Aceh district, while the program's objective was to educate the people of Central Aceh. Besides that, there are several obstacles faced, namely the factor of natural conditions, the condition of the distance to the intended school is very far considering the travel time on the trip, the availability of local wisdom reading books, the absence of additional books on local wisdom, the factor of organizational commitment, collaborating with other parties related parties. The recommendations formulated need a study on the procurement of books according to the applicable curriculum and also the existence of supporting books in creating student interest in reading and the existence of a partnership with the Central Aceh District Library and Archives Service with academics.